Reversal of cold intolerance by testosterone in orchiectomized mice after tibial nerve transection - Khalilzadeh, Emad; Aliyoldashi, Mohammadhassan; Abdkarimi, Babak; Azarpey, Farzin; Vafaei Saiah, Gholamreza; Hazrati, Reza; Caspani, Ombretta (Behavioural brain research, 2023)
Cold intolerance is a debilitating effect of nerve injury, has a strong impact on the life of patients and no advisable treatment exists against it. Testosterone influences pain pathways and has analgesic effects. A recent study showed testosterone as being an agonist of TRPM8, the predominant ion channel that contributes to cold hypersensitivity after injury. We investigated the effect of testosterone on cold sensitivity after nerve injury. Specifically, using the double plate test (DPT) (thermo-neutral-plate: 31 ºC and cold-plate: 18 ºC) we determined the thermal preference of mice at different points during the study design consisting of: orchiectomy, tibial nerve transection (TNT) (30 days after orchiectomy), 15-days-repeated subcutaneous injections of testosterone enanthate (250 or 500 µg/kg/day) or vehicle (started 12 h after TNT surgery). Different parameters such as time spent on cold plates, distance traveled, animal speed on the cold- and thermo-neutral-plates were determined in naïve, sham and neuropathic animals. Neither orchiectomy nor sham TNT surgery generate effects on cold intolerance and animal activity while TNT surgery decreased the time spent on the cold-plate and the distance traveled during DPT. Testosterone administration reversed the effect of nerve injury, decreasing the cold hypersensitivity and increasing activity of TNT mice. However, the effect of testosterone on cold avoidance reduced with time and at 14 days after TNT surgery, a higher dose was needed to reverse the effect generated by nerve injury. This indicates that although testosterone administration has a positive effect on cold intolerance, it might not be suitable for prolongated treatment.